2003
DOI: 10.1021/jm021110e
|View full text |Cite
|
Sign up to set email alerts
|

New Cytotoxic and Water-Soluble Bis(2-phenylazopyridine)ruthenium(II) Complexes

Abstract: New water-soluble bis(2-phenylazopyridine)ruthenium(II) complexes, all derivatives of the highly cytotoxic alpha-[Ru(azpy)(2)Cl(2)] (alpha denoting the coordinating pairs Cl, N(py), and N(azo) as cis, trans, cis, respectively) have been developed. The compounds 1,1-cyclobutanedicarboxylatobis(2-phenylazopyridine)ruthenium(II), alpha-[Ru(azpy)(2)(cbdca-O,O')] (1), oxalatobis(2-phenylazopyridine)ruthenium(II), alpha-[Ru(azpy)(2)(ox)] (2), and malonatobis(2-phenylazopyridine)ruthenium(II), alpha-[Ru(azpy)(2)(mal)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
75
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 32 publications
1
75
0
3
Order By: Relevance
“…The 2D NOESY NMR data show as most important cross-peaks: an interligand NOE between the H6 resonance and H14 resonance, and an interligand NOE between the H6 and CH 3 resonance. As it is known that in case of the a-Ru(azpy) 2 backbone, an H6-H(o) interligand NOE cross-peak is to be expected [11,36,37], these H6-H14 and H6-CH 3 NOEs confirm the a configuration. The fact that the H6 resonance gives an NOE to both the CH 3 signal, as well as to the H14 resonance, suggests the fast rotation of the phenyl rings in solution, a common feature of a isomeric complexes, despite the presence of the methyl groups.…”
Section: Nmr Characterization Of Complexes 1-6mentioning
confidence: 74%
See 2 more Smart Citations
“…The 2D NOESY NMR data show as most important cross-peaks: an interligand NOE between the H6 resonance and H14 resonance, and an interligand NOE between the H6 and CH 3 resonance. As it is known that in case of the a-Ru(azpy) 2 backbone, an H6-H(o) interligand NOE cross-peak is to be expected [11,36,37], these H6-H14 and H6-CH 3 NOEs confirm the a configuration. The fact that the H6 resonance gives an NOE to both the CH 3 signal, as well as to the H14 resonance, suggests the fast rotation of the phenyl rings in solution, a common feature of a isomeric complexes, despite the presence of the methyl groups.…”
Section: Nmr Characterization Of Complexes 1-6mentioning
confidence: 74%
“…The complexes a-and c-[Ru(azpy) 2 Cl 2 ] have a C 2 symmetry, causing the two azpy ligands in each isomer to be identical in NMR. It was proven that the a configuration shows a characteristic (intramolecular) interligand H6-H(o) (H(o)=H10/H14) NOE cross-peak [11,36,37]. 1 Moreover, the averaged interproton H6-H(o) distances from solid-state XRD-data appear to be useful for predicting NOEs in solution [11,36,37].…”
Section: Nmr Characterization Of Complexes 1-6mentioning
confidence: 99%
See 1 more Smart Citation
“…3 have generated tremendous synthetic activity. My lab has recently modified the azapyridine compounds and made them water soluble (91), which results in compounds with a high antitumor activity. Sadler and colleagues (92) have shown that even organometallic half-sandwich Ru compounds show activity and interesting DNA-binding properties.…”
Section: Ruthenium and Transamine Pt Compoundsmentioning
confidence: 99%
“…9 10 11 Recentemente vários tipos de complexos de Ru (11) com ligantes arenos 12 13 ou ligantes bidentados heterocíclicos 14 No caso de compostos dinucleares os mais estudados são os de cobre, focalizando principalmente as propriedades antiinflamatórias e atuação destes complexos como miméticos da SOD. 41 Os AINEs com a função ácido carboxílico, foi lavado com 2-propanol e colocado no dessecador contendo P 2 0 S e sílica-gel.…”
unclassified